Metaverse in Tourism as a Medium for Conservation of Maritime Area in Karimunjawa National Park - Muhamad Hasan Basori Basori; Agus Triyono; Muhammad Noor Hidayat; Serina Tiara Sensato; Utari Fatma Dewi (Universitas Muhammdiyah Yogyakarta, 2023)
Conservation of marine areas in Indonesia has so far been carried out conventionally on the original objects. Responding to the development of industry 4.0 and society 5.0 which leads to increasingly rapid virtual technology, the conservation of maritime areas on the island of Karimunjawa by utilizing the metaverse platform is very relevant for discussion. The method used in this paper is a qualitative method with a descriptive analysis approach based on data sourced from several kinds of literature. The results show that maritime area conservation is in line with the metaverse concept using the virtual replication of aquatic ecosystems. In this metaverse, visitors will be able to enjoy several activities and benefits such as gaining knowledge related to maritime area conservation and conducting virtual tours, conducting virtual visit simulations before visiting in person, making buying and selling transactions, and also forming social communities and tourist communities.